Excessive interdialytic weight gain and associated factors - Silva,Renata Reis de Lima e (Sociedad Chilena de Nutrición, Bromatología y Toxicología, 2021)
ABSTRACT Excessive interdialytic weight gain (IDWG) may be associated with numerous factors that are discussed little in the literature. The aim of the present study was to evaluate factors associated with excessive IDWG in patients on hemodialysis. A cross-sectional study was conducted with 197 adults on hemodialysis at a satellite clinic in the city of Jaboatão dos Guararapes, Brazil. We calculated %IDWG by the mean difference among 12 hemodialysis sessions, with >4.5% considered excessive. The conceptual model considered socioeconomic, demographic, clinical, anthropometric and laboratorial variables. Excessive IDWG was found in 28.4% of the sample. In the final adjusted Poisson regression model, three variables remained independently associated with excessive IDWG: age between 20 and 59 years (adjusted prevalence ratio [PRadjusted]= 1.87, 95% CI: 1.21-2.88), household income between one and two times the minimum monthly salary (PRadjusted=2.14, 95% CI: 1.36-3.44) and <nine years of schooling (PRadjusted= 1.78 95% CI: 1.15-2.76). The results revealed associations between excessive IDWG and some factors. The most strongly associated factor was low income, followed by non-elderly adult age and low level of schooling.